Experimental evaluation of three different configurations of constructal disc-shaped heat exchangers. (December 2017) - Capata, R.; Beyene, A.
Highlights: Branched heat exchangers experimental campaign. Efficiency and load losses evaluation. Different Branched exchangers realized and tested. Constructal theory. Comparison of the exchangers, application range and final choice. Abstract: The aim of this work is to experimentally evaluate three different compact branched heat exchangers, measuring, for every single device, the thermal efficiency and the pressure drop. The generality of the analysis of phenomena is enhanced by a comparison of the performance of different refrigerant fluids. In the first configuration, the channels have been designed, varying the inner diameter, to allow for an average constant flow speed throughout the exchanger. In the second one, the flow Reynolds number inside of the channels has been maintained constant. The last configuration is built according to the constructal diameter variation, as indicated in Bejan Constructal Theory. The exchanger manufacturing process is described in detail. The test bench has been assembled using a hot source (Heating Plate with a power of 500 W) and a submersible pump, needed for the fluid recirculation, coupled with flowmeters, to control the mass flow rate within a specific range. The data obtained from several comparative tests have been analyzed, to determine the optimal solution for each refrigerant among the different exchangers.